From Protracted Humanitarian Relief to State-led Social Safety Net System : Somalia Baxnaano Program - Al-Ahmadi, Afrah; Zampaglione, Giuseppe (World Bank, Washington, DC, 2022)
In 2019, with support from the International Development Association (IDA), the Federal Government of Somalia established its first national safety net program, the Baxnaano Program. Despite institutional challenges, political and economic fragility, the Program is delivering promising results. This paper discusses the design and implementation experience of the Baxnaano Program to (i) understand the opportunities and challenges leading to the establishment of a national safety net program in a context of high fragility, insecurity, and protracted humanitarian relief interventions; (ii) identify if and how the Program is supporting the vision to transition from protracted humanitarian response to longer-term safety net system; and iii) examines if and how the Program is supporting state-building.